Linearity improvement of gm-boosted common gate LNA: Analysis to design. (October 2016) - Sahafi, Ali; Sobhi, Jafar; Koozehkanani, Ziaddin Daei
Abstract: This paper proposes a highly linear low noise amplifier (LNA) for ultra-wideband applications. It focuses on linearization of the basic active gm-boosted common gate (CG) LNA circuit by exploring the nonlinearity coefficients using the generalized nonlinearity model. Mathematical analysis shows that in active gm-boosted CG LNA, the third input intercept point (IIP3) of LNA depends on interaction between main and auxiliary amplifiers. The multiple gated transistor (MGTR) technique, which was previously developed, is applied to an active gm-boosted CG amplifier based on linearity analysis. Also an improved shunt peaking bandwidth (BW) extension technique is proposed in this paper that extends the flat BW up to 200%. Post-layout simulation results of the proposed LNA circuit in a 180 nm RF CMOS process show +11 dBm of IIP3 that indicates 12 dB improvement comparing with conventional structures. The proposed wideband LNA has a voltage gain of 16 dB, −3 dB bandwidth from 1 GHz to 10.3 GHz, and minimum noise figure (NF) of 4.1 dB. The simulated S11 is better than −10 dB in whole frequency range while the LNA core draws 6 mA from a single 1.8 V DC voltage supply.